High-Risk genotypes associated with poor response to controlled ovarian stimulation in Indian women - Anuradha Udumudi; K Chaitra Lava; Vandana Hegde (Wolters Kluwer Medknow Publications, 2023)
Background: Infertility is a global burden and has become exceedingly common in the preceding years; controlled ovarian stimulation (COS) is a pre-requisite for couples opting to conceive via in vitro fertilisation (IVF). Based on the number of oocytes retrieved upon COS, a patient may be classified as a good responder or poor responder. The genetic aspect of response to COS has not been elucidated in the Indian population. Aims: This study aimed to establish a genomic basis for COS in IVF in the Indian population and to understand its predictive value. Settings and Design: The patient samples were collected at both Hegde Fertility Centre and GeneTech laboratory. The test was carried out at GeneTech, a diagnostic research laboratory based in Hyderabad, India. Patients with infertility without any history of polycystic ovary syndrome and hypogonadotropic hypogonadism were included in the study. Detailed clinical, medical and family history was obtained from patients. The controls had no history of secondary infertility or pregnancy losses. Materials and Methods: A total of 312 females were included in the study comprising 212 women with infertility and 100 controls. Next-generation sequencing technology was employed to sequence multiple genes associated with response to COS. Statistical Analysis Used: Statistical analysis using odds ratio was carried out to understand the significance of the results obtained. Results: Strong association of c.146G>T of AMH, c.622-6C>T of AMHR2, c.453-397T>C and c.975G>C of ESR1, c.2039G>A of FSHR and c.161+4491T>C of LHCGR with infertility and response to COS was established. Further, combined risk analysis was carried out to establish a predictive risk factor for patients with a combination of the genotypes of interest and biochemical parameters commonly considered during IVF procedures. Conclusion: This study has enabled the identification of potential markers pertaining to response to COS in the Indian population.